Effect of Liquidity, Leverage, Company Size, Audit Committee on Financial Distress - Wahyudi, Ickhsanto; Mahroji; Hanifah (LPPM STIE PPI, 2023)
Introduction/Objectives: This paper discusses the effect of liquidity, leverage, company size, and audit committee on financial distress in the hospitality, restaurant and tourism sectors. This research is important to understand the factors that influence a company's potential financial distress. Background to the Problem: Does liquidity, leverage, company size, and audit committee contribute to financial distress? Novelty: Previous research on this topic in the hospitality, restaurant and tourism sectors in Indonesia has been limited. Research Method: This study uses multiple linear regression analysis with a sample of 90 financial statement data from 18 companies for the 2016-2020 period selected by purposive sampling techniques. Findings/Results: Simultaneously, all four independent variables had a significant effect on financial distress. Partially, only liquidity, leverage and company size have a significant effect. Conclusion: Liquidity, leverage, and company size are important factors influencing potential financial distress in the sector. The implication is that companies need to manage these three factors optimally to mitigate the risk of financial difficulties